2011
DOI: 10.1002/cphc.201000876
|View full text |Cite
|
Sign up to set email alerts
|

CH⋅⋅⋅π Interaction‐Modulated Solid‐State Packing and Carrier Mobility in Thienyl and Thieno[3,2‐b]Thienyl End‐Capped Distyrylarylene Derivatives

Abstract: Research on structure-property relationships in distyrylarylene derivatives is far behind their wide applications in optoelectronic devices due to the absence of crystal structure information. Herein, the single crystals of 4,4'-bis(2-thienylvinyl)biphenyl (1) and 4,4'-bis(2-thieno[3,2-b]thienylvinyl)biphenyl (2) were successfully grown by the vapor transport method. Both molecules adopt the typical herringbone packing motif. However, the intermolecular C-H⋅⋅⋅π interaction in compound 2 is much stronger than t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…1a), including 4,4 0 -bis(2-thienyl-vinyl)biphenyl (BPVT), 4,4 0 -bis(2-bithienylvinyl)biphenyl (BBTVB), and 4,4 0 -bis(2-terthienyl-vinyl)biphenyl (BTTVB), were synthesized through the Horner-Wadsworth-Emmons reaction. 20 The details on the synthesis, purification, and characterization of the chemical properties of three compounds are provided in ESI † (Scheme S1 and Fig. S1, S2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…1a), including 4,4 0 -bis(2-thienyl-vinyl)biphenyl (BPVT), 4,4 0 -bis(2-bithienylvinyl)biphenyl (BBTVB), and 4,4 0 -bis(2-terthienyl-vinyl)biphenyl (BTTVB), were synthesized through the Horner-Wadsworth-Emmons reaction. 20 The details on the synthesis, purification, and characterization of the chemical properties of three compounds are provided in ESI † (Scheme S1 and Fig. S1, S2).…”
Section: Resultsmentioning
confidence: 99%
“…It can be identified that the monoclinic BPVT crystal belongs to the space group of P2 1 (CCDC no. 796660) 20 with cell parameters of a = 6.073 Å, b = 7.496 Å, c = 19.872 Å, and a = b = g = 901 (Table S2, ESI †). Based on the abovementioned cell parameters, the red circle and green triangle sets of spots in the SAED pattern of BPVT EHMSs (Fig.…”
Section: Structural Characterizations Of Three Microcrystalsmentioning
confidence: 99%
See 2 more Smart Citations